The Diagnostic Performance of 18F-FDG PET/CT in Recurrent Pancreatic Cancer: A Systematic Review and Meta-analysis - Gu A; Yuezhan Shan; Huasong Huo; Chao Ding; Caixia Sun (Applied Bionics and Biomechanics)
Purpose. The CT scan is the best common screening test for pancreatic cancer recurrence after surgery. The goal of our meta-analysis was to assess the diagnostic accuracy of 18F-FDG PET/CT for pancreatic cancer recurrence. Methods. We examined PubMed and Embase for suitable papers between 2009 and 2022. The researchers considered studies that looked at the diagnostic usefulness of 18F-FDG PET/CT in identifying local and/or distant disease recurrence throughout the follow-up following pancreatic cancer resection. The Quality Assessment of Diagnostic Performance Studies-2 (QUADAS-2) method was used to evaluate the quality of each study. For each of the publications included, two researchers extracted data independently. The extracted data included general data (authors, year of publication), literature characteristics (country, type of literature, and design of study), characteristics of the patient (patients’ number, mean or median age, and treatment regimen), and technical aspects (scanner, injection activity, and image analysis). Results. The analysis includes 7 trials with a total of 263 patients. The sensitivity and specificity of 18F-FDG PET/CT in detecting recurrent pancreatic cancer following definitive treatment were 0.89 (95 percent CI: 0.83-0.93) and 0.88 (95 percent CI: 0.72-0.96), respectively, according to the pooled estimates. PET/CT performed well in the diagnosis of recurrent pancreatic cancer, with an AUC of 0.94. (0.91-0.95). Conclusions. 18F-FDG PET-CT was found to be a reliable detection method in recurrent pancreatic tumor.